Sleep Apnea and Nocturnal Cardiac Arrhythmia: A Populational Study - Cintra,Fatima Dumas (2014)
Background: The mechanisms associated with the cardiovascular consequences of obstructive sleep apnea include abrupt changes in autonomic tone, which can trigger cardiac arrhythmias. The authors hypothesized that nocturnal cardiac arrhythmia occurs more frequently in patients with obstructive sleep apnea. Objective: To analyze the relationship between obstructive sleep apnea and abnormal heart rhythm during sleep in a population sample. Methods: Cross-sectional study with 1,101 volunteers, who form a representative sample of the city of São Paulo. The overnight polysomnography was performed using an EMBLA® S7000 digital system during the regular sleep schedule of the individual. The electrocardiogram channel was extracted, duplicated, and then analyzed using a Holter (Cardio Smart®) system. Results: A total of 767 participants (461 men) with a mean age of 42.00 ± 0.53 years, were included in the analysis. At least one type of nocturnal cardiac rhythm disturbance (atrial/ventricular arrhythmia or beat) was observed in 62.7% of the sample. The occurrence of nocturnal cardiac arrhythmias was more frequent with increased disease severity. Rhythm disturbance was observed in 53.3% of the sample without breathing sleep disorders, whereas 92.3% of patients with severe obstructive sleep apnea showed cardiac arrhythmia. Isolated atrial and ventricular ectopy was more frequent in patients with moderate/severe obstructive sleep apnea when compared to controls (p < 0.001). After controlling for potential confounding factors, age, sex and apnea-hypopnea index were associated with nocturnal cardiac arrhythmia. Conclusion: Nocturnal cardiac arrhythmia occurs more frequently in patients with obstructive sleep apnea and the prevalence increases with disease severity. Age, sex, and the Apnea-hypopnea index were predictors of arrhythmia in this sample.